1994
DOI: 10.1002/stem.5530120116
|View full text |Cite
|
Sign up to set email alerts
|

CD34 selection for purging in multiple myeloma and analysis of CD34+b cell precursors

Abstract: However, the mean recovery of colony forming precursor cells was only 19% f 8% in the MM samples and 30% i 9% in the control samples. The selection of CD34+ hematopoietic cells is an effective purging method in MM that may be used for autografts, provided the recovery can be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…[3][4][5] Positive selection for the CD34 ϩ antigen is currently the most frequently used purging strategy, achieving a 3-4 log tumor cell depletion in CD34 Ϫ malignancies. 6,7 Because residual tumor cells were detected after purging, 8 -10 alternative strategies including gene therapeutic approaches are being developed; viral vectors, for instance, can be used as vehicle to transport suicide genes into tumor cells. Retrovirus-based vectors are able to infect both HSCs 11,12 and tumor cells at a high frequency 13,14 and are therefore not suited for transduction of a whole stem cell graft with the aim of tumor cell purging.…”
mentioning
confidence: 99%
“…[3][4][5] Positive selection for the CD34 ϩ antigen is currently the most frequently used purging strategy, achieving a 3-4 log tumor cell depletion in CD34 Ϫ malignancies. 6,7 Because residual tumor cells were detected after purging, 8 -10 alternative strategies including gene therapeutic approaches are being developed; viral vectors, for instance, can be used as vehicle to transport suicide genes into tumor cells. Retrovirus-based vectors are able to infect both HSCs 11,12 and tumor cells at a high frequency 13,14 and are therefore not suited for transduction of a whole stem cell graft with the aim of tumor cell purging.…”
mentioning
confidence: 99%
“…In BM and PB samples of patients with multiple myeloma could be shown that because of this purification step 99.99% of tumor cells are depleted (log 3.97). 37 For multiple myeloma it could be shown that purged vs un-purged transplants did not result in different disease free or overall survival, suggesting that transplanted tumor cells did not significantly contribute to tumor relapse. 37 The most intense studied genes for chemoprotective gene therapy are MDR1 [6][7][8][9][10] and MGMT.…”
Section: Discussionmentioning
confidence: 99%
“…37 For multiple myeloma it could be shown that purged vs un-purged transplants did not result in different disease free or overall survival, suggesting that transplanted tumor cells did not significantly contribute to tumor relapse. 37 The most intense studied genes for chemoprotective gene therapy are MDR1 [6][7][8][9][10] and MGMT. [24][25][26] As drug combinations are common in most chemotherapeutic regimens, gene therapy with a combination of several genes is particularly promising and would increase the therapeutic index of combination chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] In order to reduce the risk of relapse due to the transfer of myeloma cells, several techniques that remove these cells from the transplanted products are being investigated. [14][15][16][17] One such technique is the positive selection of CD34 + cells, shown to contain the necessary precursors for both short-and long-term hematopoietic reconstitution. Since it is believed that the CD34 antigen is not expressed on clonal myeloma cells, selection of CD34 + cells from autologous mobilized peripheral blood progenitor cells may result in the reduction of myeloma contamination of these cells by several orders of magnitude.…”
mentioning
confidence: 99%